Aggressiveness of pratylenchus brachyurus to sugarcane, compared with key nematode P. zeae - Barbosa, Bruno Flávio Figueiredo [UNESP]; Dos Santos, Jaime Maia [UNESP]; Barbosa, José Carlos [UNESP]; Soares, Pedro Luiz Martins [UNESP]; Ruas, Anderson Robert; De Carvalho, Rafael Bernal [UNESP] (My University, 2013)
Pratylenchus zeae, Meloidogyne javanica and M. incognita are considered key species of nematodes in sugarcane in Brazil, but P. brachyurus is also frequently found. This study was conducted to determine the aggressiveness of P. brachyurus compared with P. zeae to sugarcane. Plants were grown in pots (100 L) in an open area with initial inoculation of 10, 100, 1,000, 10,000 and 100,000/plant for P. brachyurus and P. zeae. The nematode inocula were from in vitro, carrot-cylinder cultures. Sampling was performed every 60 days until 300 days after inoculation. At harvest, we evaluated the population dynamics of the nematodes and plant growth characteristics. The population for the initial levels of 10 and 100,000 specimens/plant, for P. brachyurus and P. zeae at 300 days after inoculation were similar. This fact shows that, upon detection of nematodes in a certain place during the planting of sugarcane, the ratoon on this area should be treated so as to control populations of P. brachyurus and/or P. zeae. The damage caused by the initial population of 10 specimens of P. brachyurus was similar to those of 10.000 specimens of P. zeae. The variety CTC 2 was classified as susceptible to P. zeae and intolerant to P. brachyurus. Compared to the control, the losses as measured by the volume and fresh weight of shoots by the nematode species were 29.82% and 40.34%, respectively. Pratylenchus brachyurus was more aggressive than P. zeae to the CTC 2 sugarcane variety.
Keywords: Host-parasitic relationship; Plant disease loss; Resistance; Root lesion nematodes; Saccharum spp.